PENGEMBANGAN E-MODUL MATA KULIAH PENGEMBANGAN KONSEP DASAR IPA JURUSAN PGSD UNIVERSITAS MUSAMUS - Syahfitriani Br Ginting; Rudolfus Ruma Bay; Sri Hanipah; Yonarlianto Tembang; Rival Hanip; Yani Amenda (Program Studi PGSD Universitas Flores, 2023)
Students' high level of learning interest has a significant impact on how well they acquire new material. To accomplish this, instructors must be able to design lessons that will boost student engagement and promote quality learning. Teaching aids in the form of E-Modules are required to understand this. The goal of this research is to create a workable and useful Flipbook-based E-Module on the topic of developing fundamental natural scientific concepts at Musamus University's PGSD Department. This research used the ADDIE research and development paradigm, however it was only concerned with the development stage. One media expert and one material expert were the subjects of this study. The study's findings demonstrated that the PGSD Study Program at Musamus University could effectively use practicum-based E-modules in science basic concept development courses. This is evident from the material expert's conclusions, which were evaluated based on the adequacy of the presentation and substance and yielded a score of 4.1 with the proper criteria. According to the right criteria, the validation results from media specialists were given a score of 4.0. Thus, it is advised that students in the Elementary Science Basic Science Concept Development course use the practicum-based E-module as learning material.